GC-MS Metabolite Profile and Identification of Unusual Homologous Cannabinoids in High Potency Cannabis sativa - Basas-Jaumandreu, Josep; de las Heras, F. Xavier C. (Planta Medica, 2020)
Phytochemical investigation of the lipids extracted from seeds of Cannabis sativa by GC-MS showed 43 cannabinoids, 16 of which are new. The extract is dominated by Δ9-tetrahydrocannabinolic acid (A) and its neutral derivative trans-Δ9-tetrahydrocannabinol-C5 (THC) Cis and trans-Δ9-tetrahydrocannabinol-C7 isomers with an ethyl-pentyl branched chain together with minor amounts of trans-Δ9-tetrahydrocannabinol with a methyl-pentyl C6 branched side chain were identified as new natural compounds. Four cannabichromene isomers with a C5 side chain are postulated to be derived from the double bond migration at the terminal isoprenyl unit. C7 cannabichromene together with the neutral and acidic forms of cannabinol-C7 were also detected. The mass spectrum of these homologues as trimethylsilyl (TMS) derivatives are presented, and the fragmentation patterns are discussed.
Keywords: Cannabinoids; Cannabis sativa; Cannabaceae; phytochemical analysis; GC-MS